THE INFLUENCE OF LEARNING ABILITY AND MORALITY ON STUDENTS' WORSHIP DISCIPLINE IN STATE ELEMENTARY MADRASAH IN PONOROGO - Layly Nur Alimah; Safira Hartiana Ramadhani; Sigit Dwi laksana; Anip Dwi Saputro (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
Learning of Akidah Akhlak gradually and holistically is directed at preparing students to have true and solid beliefs, noble morals to guide students to become good individuals spiritually and socially. Good indicators in spiritual and social include: always praying to Allah SWT, discipline in carrying out worship (thaharah, prayer, fasting), always grateful, ikhtiar, surrendering, protecting the environment, respecting others, responsibility, honesty, caring, self-confidence, and discipline. The purpose of this research is (1) to determine the significance of the effect of Akidah Akhlak learning on students' social attitudes. (2) to determine the significance of the effect of Akidah Akhlak learning on students' worship discipline. (3) to find out how significant the effect of Akidah Akhlak learning is on the social attitudes and worship discipline of students at MIN in Ponorogo. This research uses a quantitative approach using sampling techniquesCluster Random Sampling. Data collection was carried out by distributing questionnaires, observation and documentation. Data analysis assisted by the program SPSS.25 with simple linear regression formulas and multiple linear regression. The results of the analysis show: (1) Learning Aqidah Akhlak has a significant effect of 22.3% on the social attitudes of students at MIN in Ponorogo. (2) Learning Aqidah Akhlak has a significant effect of 35.5% on the worship discipline of students at MIN in Ponorogo. (3) Learning Aqidah Akhlak has a significant effect of 40% on the social attitudes and worship discipline of students at MIN in Ponorogo.